A study on performance and emission characteristics of diesel engine using Ricinus Communis (Castor Oil) Ethyl Esters - Munimathan, Arunkumar; Vinayagam, Mohanavel; Afzal, Asif; Thanikodi, Sathish; Manickam, Ravichandran; Khan, Sher Afghan; Abdullah, Nur Azam; Azami, Muhammad Hanafi; Asif, Mohammad (MDPI, 2021)
Countries globally are focusing on alternative fuels to reduce environmental pollution. An example is biodiesel fuel, which is leading the way to other technologies. In this research, the methyl esters of castor oil were prepared using a two-step transesterification process. The respective properties of the castor oil (Ricinus Communis) biodiesel was estimated using ASTM standards. The effect of performance and emission on diesel engines was noted for four various engine loads (25%, 50%, 75%, and 100%), with two different blends (B5 and B20) and at two different engine speeds (1500 and 2000 rpm). The study determined that B5 and B20 samples at 1500 rpm engine speed obtained the same power, but diesel fuel generated greater control. The power increased at 2000 rpm for B5 samples, but B20 samples, as well as diesel, were almost the same values. In the 40–80% range, load, and load values were entirely parallel for each load observed from the engine performance of the brake power in all samples.